Judaism today - Cohn-Sherbok, Dan (Religion today (London, England), 2010)
This title provides a concise introduction to contemporary challenges and key issues facing Judaism. The contents cover sources of authority, the effects of the Jewish Enlightenment, the religious impact of the Holocaust, and much more.